Which terms should be used to describe autism? Perspectives from the UK autism community. (May 2016) - Kenny, Lorcan; Hattersley, Caroline; Molins, Bonnie; Buckley, Carole; Povey, Carol; Pellicano, Elizabeth
Recent public discussions suggest that there is much disagreement about the way autism is and should be described. This study sought to elicit the views and preferences of UK autism community members – autistic people, parents and their broader support network – about the terms they use to describe autism. In all, 3470 UK residents responded to an online survey on their preferred ways of describing autism and their rationale for such preferences. The results clearly show that people use many terms to describe autism. The most highly endorsed terms were 'autism' and 'on the autism spectrum', and to a lesser extent, 'autism spectrum disorder', for which there was consensus across community groups. The groups disagreed, however, on the use of several terms. The term 'autistic' was endorsed by a large percentage of autistic adults, family members/friends and parents but by considerably fewer professionals; 'person with autism' was endorsed by almost half of professionals but by fewer autistic adults and parents. Qualitative analysis of an open-ended question revealed the reasons underlying respondents' preferences. These findings demonstrate that there is no single way of describing autism that is universally accepted and preferred by the UK's autism community and that some disagreements appear deeply entrenched.